IMPLEMENTASI PEMBELAJARAN MENDALAM DAN BERDIFERENSIASI DALAM KURIKULUM MERDEKA UNTUK MEWUJUDKAN PEMBELAJARAN BERMAKNA - Amalia Ramadani; Amalia Sundari; Atikah Aini Nasution (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The implementation of the Merdeka Curriculum encourages student-centered, meaningful learning by applying deep and differentiated learning. Yet, adopting these two approaches continues to face significant challenges, particularly regarding teachers' preparedness and understanding when using them in class. This study seeks to investigate the implementation of deep learning and differentiated learning in the Merdeka Curriculum, including their role in attaining meaningful learning outcomes. It adopts a qualitative approach through a literature review (library research). Data were collected by searching diverse relevant scholarly sources and examined through content analysis techniques. The research results indicate that deep learning helps bolster conceptual understanding, critical thinking skills, and active student involvement, whereas differentiated learning provides customized learning opportunities based on students' needs, interests, and traits. Even though its rollout hasn't hit peak effectiveness, these approaches mutually reinforce each other to advance learning that's more vibrant, flexible, and profound in significance.